PRODUKSI BIODIESEL DARI BIOMASSA Chlamydomonas sp. ICBB 9113 DIKULTIVASI MENGGUNAKAN MEDIA YANG MURAH: EFEKTIFITAS DARI BEBERAPA METODE EKSTRAKSI - Patmawati Patmawati; Bustami Ibrahim; Iriani Setyaningsih; Untung Sudadi (Widyariset, 2014)
The main challenges to overcome in biodiesel production from microalgae are lower oil yield, as compared to those derived from plant and animal biomass, and expensive culture media. This work was aimed to compare the effectivity of three extraction methods differed in solvent used, e.g. n-hexane (N-hex), ethanol (Eth), and mixture of chloroform-methanol-water (CMW), to extract crude lipid and biodiesel from dry biomass of Chlamydomonas sp. ICBB 9113. This microalgae was cultivated in a cheap culture media using N and P soil fertilizers as nutrient sources. The results showed that, by using N-hex, Eth, and CMW methods, it could be extracted, respectively, 0.06%, 4.51%, and 20.45% crude lipid, and 384.2, 1333.8, and 2430.6 mg/100g biodiesel. The fatty acid profile of the studied microalgae biomass was: C8:0 (0.11%), C10:0 (0.09%), C14:0 (7.70%), 16:0 (1.39%), C18:0 (0.85%), C14:1 (5.12%), C16:1 (7.09%), C18:1 (8.28%), C18:2 (12.80%), and C18:3 (42.57%). Fatty acid characterization showed that Chlamydomonas sp. ICBB 9113 was dominated by C18: 3 and C16:0. Therefore, these microlagae were suitable to be used as raw material for biodiesel production to substitute the conventional fuel.